Paternal Occupation and Delirium Risk in Older Adults: A Potential Marker of Early-Life Exposures. Issue 5 (8th August 2022) - Shiff, Haley M; Arias, Franchesca; Dufour, Alyssa B; Carr, Deborah; Chen, Fan; Gou, Yun; Jones, Richard; Schmitt, Eva; Travison, Thomas G; Kunicki, Zachary J; Okereke, Olivia I; Inouye, Sharon K
Abstract: Background and Objectives: Delirium is a common disorder among older adults following hospitalization or major surgery. Whereas many studies examine the risk of proximate exposures and comorbidities, little is known about pathways linking childhood exposures to later-life delirium. In this study, we explored the association between paternal occupation and delirium risk. Research Design and Methods: A prospective observational cohort study of 528 older adults undergoing elective surgery at two academic medical centers. Paternal occupation group (white collar vs. blue collar) served as our independent variable. Delirium incidence was assessed using the Confusion Assessment Method (CAM) supplemented by medical chart review. Delirium severity was measured using the peak CAM-Severity score (CAM-S Peak), the highest value of CAM-S observed throughout the hospital stay. Results: Blue-collar paternal occupation was significantly associated with a higher rate of incident delirium (91/234, 39%) compared with white-collar paternal occupation (84/294, 29%), adjusted odds ratio OR (95% confidence interval [CI]) = 1.6 (1.1, 2.3). All analyses were adjusted for participant age, race, gender, and Charlson Comorbidity Index. Blue-collar paternal occupation was also associated with greater delirium severity, with a mean score ( SD ) of 4.4 (3.3), compared with white-collar paternal occupation with a mean score ( SD ) of 3.5 (2.8). Among participants reporting blue-collar paternal occupation, we observed an adjusted mean difference of 0.86 (95% CI = 0.4, 1.4) additional severity units. Discussion and Implications: Blue-collar paternal occupation is associated with greater delirium incidence and severity, after adjustment for covariates. These findings support the application of a life-course framework to evaluate the risk of later-life delirium and delirium severity. Our results also demonstrate the importance of considering childhood exposures, which may be consequential even decades later.